PENGARUH MODEL PEMBELAJARAN CONNECTING ORGANIZING REFLECTING EXTENDING (CORE) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK FASE F SMA NEGERI 5 PADANG - Roza, Elfira; Dwina, Fitrani (Jurnal Edukasi dan Penelitian Matematika, 2024)
- Students want to master math topics. The conceptual knowledge of Phase F students at SMA Negeri 5 Padang is poor. CORE helps children learn math. This study compares the CORE learning paradigm to normal learning methods to increase arithmetic comprehension. The study examined SMA Negeri 5 Padang Grade XI students' arithmetic knowledge. The study used a posttest-only non-equivalent control group. Final essay tests tested experimental and control groups' mathematical understanding. Data analysis yielded 0.000 P-value. Strong evidence rejects the null hypothesis () with a P-value below α. The CORE learning technique helped SMA Negeri 5 Padang Class XI IPA students understand arithmetic better than the traditional strategy.Keywords– Connecting Organizing Reflecting Extending  Model, Understanding Mathematical Concepts, Conventional Learning